11C-labeling and preliminary evaluation of pimavanserin as a 5-HT2A receptor PET-radioligand. Issue 5 (1st March 2015) - Andersen, Valdemar L.; Hansen, Hanne D.; Herth, Matthias M.; Dyssegaard, Agnete; Knudsen, Gitte M.; Kristensen, Jesper L.
Graphical abstract